The young unicorns - L'Engle, Madeleine (Dell Pub. Co, 1968)
A seventeen-year-old boy, former member of a tough New York gang, a blind and talented twelve-year-old musician, the Austin family, and Canon Tallis are among the key characters who become involved in a frightening and evil scheme relying on the ability of a refined laser to give complete power over people's minds.